Valuation of 5G mmWave Fixed Wireless Access in Residence Area: Analysis of Real Option for Wireless Broadband Service in Kota Wisata Cibubur Using Decision Tree and Black Scholes Model - May Hendra Panjaitan; Catur Apriono (Universitas Ahmad Dahlan, 2022)
Fixed Wireless Access (FWA) is one of the popular use cases in 5G, expected to replace conventional internet service. However, investing in a telecommunications project requires massive capital, so careful planning is usually required. In general, investments are valued by the standard Net Present Value (NPV) method. When the NPV is positive, the project is profitable. However, the NPV possibly will not be as expected due to uncertainty in the future. One of these is the number of subscribers. This research proposes using Real Option (RO) to analyze the FWA project with an uncertainty of the number of subscribers and compare it to the standard NPV method. From the result of the research, the standard NPV method produces a positive Expected NPV of 153,176. However, there is a 33% possibility that the NPV will be -406,246. By using the decision tree in RO to evaluate the project, the managers have an option to delay the project from one to three years and eliminate negative NPV resulting in the Expected NPV of 250,038, 216,842, and 188,371. Using Black Scholes Model to delay the project from one to three years also results in a higher Expected NPV of 220,668, 209,593, and 219,428.